Revitalasi Layanan Sirkulasi Perpustakaan Perguruan Tinggi - Isran Elnadi Margareta (THE LIGHT : Journal of Librarianship and Information Science, 2022)
This article discusses the revitalization of university library circulation services. The method used in thisarticle is a literature review. Materials that have been obtained through this literature review are collected,reviewed and then analyzed. Based on the results of the studies that have been carried out, it is found thatcirculation services are provided to assist users in finding information and speed up the process of borrowingback collections, because circulation services already use automation with the Slims application. Thepurpose of this circulation service is so that users can utilize the collection as much as possible,effectively, efficiently. The circulation service functions are, 1). Center for the preservation of science, 2).Learning center, 3). Teaching center, 4) Research center, 5) Information dissemination center. The servicesystem used is an open service system (open access), where the user is free to take the collection on theshelves as desired. Revitalization of this circulation service, can serve users in searching for information,ordering collections, borrowing library materials, calculating late collection fines, making visitor statistics,finding out statistics on borrowed collections to be fast, precise and accurate, improving service quality,meeting needs that cannot be met. done manually, increasing the effectiveness and efficiency of the libraryby using automation.